In California. F.r.t.l: Goldie Eben, Souchy, Ida Lehren. The 4th person is either Michael Lehren or Abe Vinocom. One of them is taking the picture; notice the shadow
In California. F.r.t.l: Goldie Eben, Souchy, Ida Lehren. The 4th person is either Michael Lehren or Abe Vinocom. One of them is taking the picture; notice the shadow.